Simulating the performance of HOV lanes for optimal urban traffic management - Alireza Naseri; Faraz Estelaji; Ali Samani; Reza Omidifar; Rahim Zahedi; Hossein Yousefi (Transportation Research Interdisciplinary Perspectives, 2024)
Traffic congestion is a significant problem in crowded cities, resulting in increased travel times, air pollution, and reduced productivity. High-occupancy vehicle (HOV) lanes have emerged as a promising solution to tackle these issues. HOV lanes are reserved for vehicles carrying multiple passengers, incentivizing shared travel and reducing the number of low-occupancy vehicles on the road like school buses. By reducing the overall number of cars on the road, HOV lanes can significantly alleviate traffic congestion, improve travel times, and reduce air pollution. The effectiveness of HOV lanes depends on the degree of demand for shared travel and the availability of incentives, such as employer-provided benefits or toll exemptions. Additionally, the design and implementation of HOV lanes must be carefully planned to ensure that they do not negatively impact other road users. Tehran, as one of the largest and most populous cities in Asia, is a major destination for daily travel by workers. The Tehran-Karaj freeway serves as the primary and busiest entrance to Tehran city, experiencing heavy traffic every day in the morning towards Tehran and in the evening towards Karaj. In this study, the traffic conditions of this freeway were simulated in the existing state and with the presence of HOV lanes, and the resulting traffic parameters were compared and analyzed under different traffic scenarios. The findings of this research can offer valuable insights for decision-makers and traffic policy makers.